Male Infertility Problems and Solutions - Sabanegh, Edmund S.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2011)
Male Infertility: Problems and Solutions provides a summary of state of the art developments in male infertility for both new and experienced practitioners. Written in a clear, concise and readable style, this volume allows the reader to obtain rapid answers to this challenging medical issue. Special emphasis is placed on diagnostic and treatment algorithms. Topics covered include interpretation of semen analysis and advanced testing, endocrine and genetic evaluation, diagnosis of azoospermia as well as an up-to-date interpretation and analysis of the many new therapies available for the treatment of male factor infertility. Male Infertility: Problems and Solutions provides rapid acquisition of pertinent background and development of management plans through the use of concise discussion and treatment algorithms and thus will be of great value to general urologists, gynecologists, primary care providers and allied health providers who manage infertility in both men as well as women.
The Initial Consultation for Male Infertility. - Interpretation of Basic Semen Analysis and Advanced Semen Testing -- Azoospermia: Diagnosis and Management -- Ejaculatory Dysfunction -- Genetic Issues with Male Fertility -- Endocrinopathies -- Female fertility: Implications on Management of Male Factor -- Varicocele--To fix or not to fix -- Medical Management of Male Infertility -- Surgical Reconstructions of Obstruction -- Techniques for Sperm Harvest -- Sperm Banking--When, Why and How? -- Assisted Reproduction--Which Type is Right? -- Ethical Dilemmas with Infertility.
Keywords: Medicine; Reproductive Medicine; Surgery; Urology; Medicine & Public Health; Urology/Andrology.; Reproductive Medicine; Surgery